PENERAPAN COOPERATIVE LEARNING TIPE STAD DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA XI.5 UPT SMAN 9 BONE - Dilla Sasmita; Delfia Gusninda Sari; Nurpadilla; Andi Ikram Efendy; Emmi Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the application of STAD (Student Teams Achievement Division) type Cooperative Learning in improving student learning motivation at UPT SMAN 9 Bone. This research used Classroom Action Research (CAR) method with two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 30 students of class XI.5 at UPT SMAN 9 Bone. Data collection was conducted through observation, motivation questionnaires, and documentation. The results showed that the application of STAD-type cooperative learning significantly improved student learning motivation. In cycle I, the percentage of students with high motivation reached 60%, and in cycle II it increased to 86.67%, exceeding the predetermined success criterion of 80%. The improvement was driven by active student participation in heterogeneous group activities, peer discussions, individual quizzes, and team rewards. The conclusion of this study confirms that STAD-type cooperative learning is effective in improving student learning motivation and is recommended to be implemented as an innovative learning strategy in senior high schools.